Uji Kandungan Boraks pada Makanan Berbahan Dasar Daging dengan Menggunakan Ekstrak Kunyit dan Ekstrak Bawang Merah yang Dijajakan di Sekolah Dasar di Kecamatan Percut Sei Tuan - Putri Larasati; Abdul Karim; Ida Fauziah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
The research was conducted to investigate the existeme of borax in food producte which were made from meat. The research was carried descriptively by collecting 60 samples consists of 20 meatball samples, 20 sausage samples and 20 nugget samples from food seller in 20 elementary school in Percut Sei Tuan. The result showed that none of samples contained borax.